BLOOD GLUCOSE RESPONSE AND GLYCEMIC INDEX OF SOME DRIED LEGUMES IN NORMAL HUMAN SUBJECTS - Abdullah M. Thannoun (Mesopotamia Journal of Agriculture)
Blood glucose response and glycemic Index (GI) for broad bean kernels, whole broad bean, chickpea, lentils and kidney bean in normal human subjects using glucose as standard were studied. Twenty one male normal human subjects (age 22-35 years and body mass index, BMI 22-26 kg/m²) were chosen as volunteers for this study. The subjects were divided randomly into groups where each three or four of the subjects could submit to the experiments. After 12 hours overnight fast each subject was tested for blood glucose at 0 time before given the test food or glucose standard in an amount to provide 50 g carbohydrate. Glycemic response, Incremental Area under the Curve (IAUC) and Glycemic Index (GI) were determined and calculated. The results show that there were significant (P<0.05) differences between the IAUC and GI of legumes in normal subjects. The respective GIg (GI when glucose as standard) values for the broad bean kernels, whole broad bean, chickpea, lentils and kidney bean were 66, 53, 36, 22 and 26 compared with 100 for glucose standard. The highest IAUC value (159 mmol. min/L) was resulted after the ingestion of broad bean kernels compare with the lowest value (54 mmol.min/L) after the ingestion of lentils. Comparable and similar gradient values of GIb (GI when white bread as standard) for the same legumes were resulted. It was concluded that legumes such as lentils, chickpea and kidney bean elicited very low GI, whereas whole broad bean and broad bean kernels gave medium GI. Therefore, it was suggested that the legumes which have lower GI could be used in the diet management of diabetic therapy of type II diabetes.